Diálogos e possibilidades entre o movimento Bauhaus, a etnomatemática e a educação matemática realística - Boaventura, Marcelo (2011)
The objetive of this research is to establish between geometry and a school that dealt with practical issues of Architecture, Art and Design and hás a lot of geometry to the school of Arts and Architecture Bauhaus. Whereas the educational phenomena present in this movement for Art and Architecture establish connections with Realistic Mathematics Education (E.M.R.) and Ethnomathematics, did historical research since this school and the two theories argue that knowledge can emerge from the practical issues day-to-day. We conducted two interviews with two professors of mathematics that deals with the real context and discurs the possibility of mathematics as a bridge catalyst, to explain, measure and guess the phenomena that are in different areas and social contexts, especially Art, Architecture and Design. The theoretical and methodological foundations are in dialogue with the E.M.R., Ethnomathematics and the Bauhaus. The interview was based on these theories and historical processes of the Bauhaus. The interview was based on these theories and historical processes of the teaching and learning of geometry with the three-dimension constructions as instruments of the Art and Crafts. It is a qualitative research interview as having the tools to collect data in the coding an decoding theory and practice